The Role of Blinks, Microsaccades and their Retinal Consequences in Bistable Motion Perception - Brych, Mareike; Murali, Supriya; Händel, Barbara (Frontiers in Psychology, 2021)
Eye related movements such as blinks and microsaccades are modulated during bistable perceptual tasks. However, if they play an active role during internal perceptual switches is not known. We conducted two experiments involving an ambiguous plaid stimulus, wherein participants were asked to continuously report their percept, which could consist of either uni-directional coherent or bi-directional component movement. Our main results show that blinks and microsaccades did not introduce perceptual switches. On the contrary, a reduction in eye movements preceded the perceptual switch. Blanks, on the other hand, thought to mimic the retinal consequences of a blink, consistently led to a switch. The timing of the blank-introduced perceptual change suggests that the reduction in blink probability co-occurred with the internal perceptual switch. Additionally, our results indicate that distinct internal processes underlie the switch to coherent vs. component percept. Blanks exclusively facilitated a switch to the coherent percept, and only the switch to coherent percept introduced an increase in blink rate. In a second study, we largely replicated the findings, and included a microsaccade analysis. Microsaccades only showed a weak relation with perceptual switches, but their direction was correlated with the perceived motion direction. Nevertheless, our data suggests an interaction between microsaccades and blinks by showing that microsaccades were differently modulated around blinks compared to blanks. This study shows that a reduction in eye movements precedes internal perceptual switches indicating that the rate of blinks can set the stage for a reinterpretation of sensory input. The difference in blink rate modulation succeeding the switch between different perceptual outcomes further suggests that blinks can uncover distinct internal perceptual processes that might otherwise be hard to dissociate.